EXPLORING EFFECTIVE ENGLISH LANGUAGE TEACHING METHODOLOGIES FOR MODERN CLASSROOMS (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article examines the key methodologies used in English language teaching (ELT), focusing on communicative language teaching (CLT), task-based language teaching (TBL), and blended learning. These methods represent a shift from traditional grammar-focused approaches to more interactive and learner-centered strategies. The paper highlights the advantages and challenges of each method, emphasizing their relevance in modern educational contexts.